High‐Performance Coplanar Dual‐Channel a‐InGaZnO/a‐InZnO Semiconductor Thin‐Film Transistors with High Field‐Effect Mobility. (20th January 2021) - Billah, Mohammad Masum; Siddik, Abu Bakar; Kim, Jung Bae; Yim, Dong Kil; Choi, Soo Young; Liu, Jian; Severin, Daniel; Hanika, Markus; Bender, Marcus; Jang, Jin
Abstract: An amorphous indium gallium zinc oxide (a‐IGZO) layer is deposited on very thin conductive amorphous indium zinc oxide (a‐IZO) thin film to demonstrate high‐performance, coplanar thin‐film transistors (TFTs) with dual‐channel oxide semiconductor architecture. Based on material properties, a conduction band offset (∆ E C ) of ≈0.28 eV between a‐IZO and a‐IGZO layers and a conduction band bending of ≈0.3 eV at a‐IGZO/gate insulator (GI) interface exist. Through the electrical characterization, high field‐effect mobility (μFE ) of ≈50 cm 2 V −1 s −1, a positive threshold voltage ( V Th ) of ≈2.3 V, and low off‐current ( I OFF ) of <1 pA in coplanar a‐IZO/a‐IGZO TFT are demonstrated. The electron accumulation (>5 × 10 18 cm −3 ) at both the a‐IZO/a‐IGZO and a‐IGZO/GI interfaces confirm the dual‐channel conduction. The bottom a‐IZO channel significantly contributes to increasing drain current ( I D ) due to large electron density (≈10 19 cm −3 ). The dual‐channel coplanar TFT with a‐IGZO/IZO provides a guideline for overcoming the trade‐off between high μFE and positive V Th control for stable enhancement mode operation with increased I D . Abstract : Coplanar thin‐film transistor (TFT) with a combination of low mobility amorphous InGaZnO and high mobility amorphous InZnO semiconductors is proposed for high mobility, low off‐current, and positive threshold voltage ( V Th ) for large‐area display applications. The TFTs exhibit a high mobility of 49.5 cm 2 V −1 s −1 with positive V Th (2.30 V).